Dark personalities in the workplace - Mathieu, Cynthia (Academic Press, 2021)
Dark Personalities in the Workplace defines dark personalities, their prevalence in the workplace, and how they are best managed. The book brings together research in psychology and business to both profile these employees and impart best practices for businesses to manage them. Chapters explore narcissism, Machiavellianism, and psychopathy in a work context. Coverage includes common behaviors such as incivility, negative attitudes, counterproductive behavior and escalating to harassment, bullying, violence, and fraud. Practical advice is given on how to avoid hiring dark personalities, avoid promoting dark personalities, and how to perform investigations and interventions with dark personalities. With a background in forensic psychology and industrial/organizational psychology, Cynthia Mathieu provides a researched understanding to these personalities, case studies to better understand them, and practical tools and applied solutions for dealing with them.--